Pendekatan Uswah Hasanah Dan Pengaruhnya Terhadap Regulasi Diri Siswa - Hilyatussu’ada, Hilyatussu’ada; Khusnia, Alfun (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
Self regulation is an individual effort to self-regulate in an activity by involving the ability of metacognition, motivation, and active behavior. These three aspects are applied in learning. One of the methods used to increaseself regulation students in learning is an approachUswah hasanah, where the teacher gives a good example and is seen directly by students. The purpose of this study was to determine the effect of the approachUswah hasanahon self-regulation students at MA Mathla'ul Huda Bandung. The study used a quantitative approach with a sample of 61 students (22 boys and 39 girls) in class XII. Sampling through questionnaires or questionnaires with techniquesprobability sampling by methodrandom sampling. Data analysis used a simple linear regression technique with the help of IBM SPSS 25for windows. The results of the study show that there is a significant influence between the approachesUswah hasanahon self-regulation of students in MA Mathla'ul Huda, with a significance value of 0.000 (Ï <0.05) and an influence level of 27.7%.